Artificial Neural Networks: Dual‐Gated MoS2 Memtransistor Crossbar Array (Adv. Funct. Mater. 45/2020). (4th November 2020) - Lee, Hong‐Sub; Sangwan, Vinod K.; Rojas, William A. Gaviria; Bergeron, Hadallia; Jeong, Hye Yun; Yuan, Jiangtan; Su, Katherine; Hersam, Mark C.
Abstract : In article number 2003683, Mark C. Hersam and co‐workers present dual‐gated MoS2 memtransistors, which enable a crossbar architecture that solves two long‐standing issues in neuromorphic computing hardware. In particular, one gate suppresses crossbar sneak currents while the second gate allows tuning of the synaptic learning rate. This gate‐tunability provides a dynamic means of achieving linear and symmetric potentiation and depression, thereby facilitating efficient implementation of artificial neural networks.